Letramento (trans)mídia na educação de surdas: um estudo de caso na Universidade Estadual de Goiás - (:unkn) unknown (Universidade Estadual de Goiás, 2024)
The approaches to the context of (trans)media literacy stand out for their multisemiotic possibilities in their productions and highlight the importance of critical thinking on digital platforms. These aspects indicate a favorable field for discussing different approaches to Deaf education in Higher Education. The research entitled "(Trans)media literacy in deaf education: a case study at the State University of Goiás" is linked to the line of research in Language and Social Practices of the Interdisciplinary Postgraduate Program in Education, Language and Technologies (PPG-IELT), at the State University of Goiás - UEG; and is part of the research group Literacies, Culture, Connectivity and Education (LECCE). The central question that guided this research was: how do notions of (trans)media literacy reverberate in the context of Deaf education in Higher Education? The question is unfolded from the general objective of understanding the possibilities and implications of (trans)media literacy in the context of learning and academic autonomy of a Deaf student. The theoretical foundations for the empirical discussion derive from the perspective of Digital Culture (Felinto, 2011, 2013), Jenkins (2008), Jenkins, Ford, and Verde (2013), and Santaella (2021). Next, we explore the understanding of Media and Information Literacy and trans(media) literacy in the educational context, based on Scolari (2018b), Wilson et al. (2013), and Palioura and Dimoulas (2022). To address translingualism in higher education in the context of deafness, we added the contributions of authors such as Strobel (2008), Quadros (2019), Cavalcante and Stumpf (2023), Canagarajah (2013), García (2009, 2020), Nogueira (2020) and Zilio (2023). Dewey (2023) was consulted to understand the meanings of informal learning on digital platforms, emphasizing experience in perceiving the world and interpreting the products of that perception (Rodrigues, 2017). The research adopts an exploratory qualitative methodological approach, using a single case study with a Deaf student enrolled in a degree course in Languages/English. A semi-structured script was used to collect the narratives, together with participant observation. The research site was the State University of Goiás at the Nelson de Abreu Júnior University Unit of Socio-Economic and Human Sciences in the municipality of Anápolis-GO. The results point to two units of meaning that perform in (trans)media literacy and academic autonomy, which reflects approaches to multimodality and translingualism. This is evident in the skills demonstrated by the participant in critically analyzing information from digital platforms, managing emotions, negotiating dialogue with Deaf people from other locations, ethical responsibility, participating, and navigating between different digital platforms. We believe that the most significant challenge in disseminating (trans)media literacy may be to lead the student to realize the ideologies implicit in the information she shares, becoming aware that her practices can be reconstructed and disseminated in a way that contributes to civic and humanitarian issues. We understand that the challenges posed to (trans)media literacy in Deaf education in Higher Education also reverberate around issues of training, access, linguistic and sociosemiotic resources. We also consider dialoguing with the possibilities of bilingualism as a resource to teach Portuguese as an additional language, making it possible to remain in higher education, permeated with meanings and senses.
"Transmedia Literacy in Deaf Education: a case study at the State University of Goiás"
Keywords: Educação de Surda - Ensino Superior; Educação de Surda - Letramento transmídia; Educação de Surda - Letramento midiático - Multimodalidade - Ensino Superior; Deaf education - Higher education; Deaf education - Transmedia literacy; Deaf education - Media literacy - Multimodality - Higher education; CIENCIAS HUMANAS::EDUCACAO